Programação fetal por obesidade hipotalâmica e periodontite promove hipotrofia no músculo Tibial anterior de ratos Wistar - Conrad Costa, Liziane Nunes (2021)
Fetal programming is related to insults or stimuli capable of promoting metabolic and physiological changes in the fetus, making it more susceptible to developing chronic noncommunicable diseases in adulthood. However, the effects of systemic inflammatory diseases on the skeletal muscle health of offspring are poorly understood. This study aimed to investigate the effects of fetal programming by hypothalamic obesity and experimental periodontitis, in associated and in isolated way, on the morphology of the tibialis anterior muscle of Wistar rats offspring. The analyses were performed on first-generation (F1) animals. After the birth of generation (P), males were separated for further crossbreeding and females were randomly assigned to two groups. Half of the rats were induced to hypothalamic obesity (OH) by injections (4 g/Kg/day) of monosodium glutamate (MSG) (OHP, n=30) and the remainder were administered hyperosmotic saline solution (CTL, n=30). At 70th day of age, 15 females from each group were submitted to experimental periodontitis (PE) by ligation method and subsequently redistributed into four parental groups: parental control group (CTL n=15), parental PE group (PE n=15), parental OH group (OH n=15) and obesity + periodontitis group (OH-PE n=15). After seven days, five animals from each group were euthanized to confirm the presence of PE by radiographic analysis, and OH by Lee index and weight of perigonadal and retroperitoneal fat. Seven days after ligation, the rats, PE group, were also crossed with control rats (ratio 2:1). After the birth of the first- generation animals, 20 male rats composed the four study groups (n=5/group). At 120th day of age the F1 animals were euthanized, the tibialis anterior muscles were collected, processed for morphological and histomorphometric analysis of the fibers in hematoxylin and eosin stain, of the neuromuscular junctions in nonspecific esterase reaction, and in Masson's trichrome for quantification of intramuscular connective tissue. Statistical analysis was performed using the SPSS 20.0® program, the data were evaluated by the Generalized Linear Model, followed by the LSD post-test. For all analyses, p<0.05% was adopted for statistical significance. The histomorphometric and morphological results revealed that maternal diseases promoted muscle changes in the F1 offspring in all variables analyzed, suggesting a process of muscle atrophy, more expressive in OH-PE. As for the estimated percentage of connective tissue, all groups showed changes, but in OH-PE the effects were more significant, with an increase of 20.7% compared to the control group. No changes were detected in neuromuscular junctions in F1, and there was no significant difference in the variables analyzed. At this juncture, this study revealed that fetal programming triggered by systemic inflammatory diseases, such as hypothalamic obesity and periodontitis, promoted alterations in morphological and histomorphometric parameters and in the percentage of connective tissue in the tibialis anterior muscle of the offspring, whose injuries are more expressive when maternal diseases are associated.